Effet de l’addition de fibres de coco traitées à la potasse sur les propriétés mécaniques des matériaux de construction à base d’argile – ciment - Djohore Ange Christine; Djomo Agré Séraphin; Boffoue Moro Olivier; Emeruwa Edjikémé (European Scientific Journal, ESJ, 2018)
Clay is a raw material commonly used for the construction of building materials, thanks to the different stabilization techniques used. These claybased materials have very improved properties when they contain potashtreated vegetable fillers. Thus, coconut fibers, agricultural waste from wad treatment, coconut palm fruit wrap (Cocos nucifra) and treated with a potassium hydroxide solution were used for making clay materials and stabilized with cement. Its objective is to study the influence of these fibers on the properties of the material. To achieve this objective, mortars composed of clays stabilized with 8 % cement and fibers at different levels (0.2, 0.4, 0.6 and 0.8%) for a constant length of 30 mm, been developed. These different mortars with those containing no fibers were subjected to flexural and compression tests. The results obtained show that the addition of fibers improves the mechanical performance of clay mortars stabilized with 8% cement. Especially when these fibers are treated with solution of potash. The treatment of coconut fibers with the traditional potash solution made it possible to increase the maximum stress of the fiber mortar by 13% and by 5% their stiffness compared with untreated fibers. The fiber-matrix adhesion becomes stronger with fiber treatment by 8% by weight of potash.